Morphological Traits, Productive Performance and Genotyping Fat Deposition PPAR Gene in Gama Ayam Crossbreeds of Female F1 Kamper and Male BC1 Kambro - Isna Mustafiatul Ummah; I Wayan Swarautama Mahardhika; Budi Setiadi Daryono (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
On the recent classification of native Indonesian chicken, there are 31 breeds of chicken. Highly circulated chicken breed in Indonesia is fast-growing broiler that includes several strains such as Cobb 500, Hubbard, Hybro, Isa Hyline, and Hisex. Fast-growing broiler chickens have rapid growth, with excessive fat deposition on chicken carcass which implicates a health problem and unfavorable meat quality. Gama Ayam Research Team conducted selective breeding which produces two new chicken breed Kamper and Kambro. Further selective breeding then crossbred female F1 Kamper and male BC1 (backcross I) Kambro. In this research morphological traits, productive performance and genotyping of PPAR gene related to fat deposition gene and blood lipid content in Gama Ayam were identified. Based on data analysis hybrid chickens morphological traits it concluded that Gama Ayam has a significant variation based on feather color. The productive performance was determined with the feed-conversion ratio (FCR) value which was 3.17. Genotyping of PPAR gene resulted in four polymorphisms that formed 14 haplotypes groups. Based on blood lipid content analysis of cholesterol content, triglycerides content, HDL and LDL, Gama Ayam have significantly lower content of cholesterol (107.05 mg/dl), LDL (44.71 mg/dl) and triglycerides (22.41 mg/dl). PPAR gene polymorphisms are not correlated with blood lipid content in Gama Ayam. A significantly strong correlation between PPAR gene polymorphism on the bodyweight of Gama Ayam at 49-days-old. Triglyceride level, cholesterol level and LDL level in Gama Ayam were lower than broiler chicken. Further research with a larger population size and sex classification of hybrid chicken must be conducted to validate the results.